Effectiveness of online advertising types: comparison of Banner ads and paid search ads - Canlı, Mert. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
In recent years, Internet usage rates have rapidly increased in the world. People started to use Internet in their daily lives and spend more time on Internet. As a result of this trend, online advertising has become popular among marketers. In addition, the interactivity that Internet provided was another reason for marketers to discover online advertising. Related to this many researches were conducted regarding online advertising to understand it and provide insights for marketing executives. The aim of this study is to compare the most popular online advertising types; banner ads and paid search ads. This comparison was researched in terms of beliefs, attitudes and purchase intentions related to banner ads and paid search ads from Turkish consumers‟ perspective. The findings show that Turkish consumers have more positive beliefs about and purchase intentions after seeing banner ads when compared to paid search ads. On the other hand, Turkish consumers have more positive attitudes towards paid search ads.
Keywords: Internet advertising.; Internet marketing.; Online social networks.